The Effect of Social Media Marketing on Purchase Intention through Brand Image and Brand Trust - Muhammad Farraas Al-Faruq; Adhi Prasetio (Economic and Business Horizon, 2026)
The rapid growth of Indonesia’s coffee shop industry has intensified competition and increased the importance of social media in influencing consumer purchasing behavior. This study examines the effect of Social Media Marketing Activities (SMMA) on Purchase Intention, mediated by brand trust and brand image among consumers. Motivated by Tomoro Coffee’s rapid expansion despite low consumer preference, this quantitative study applies the Stimulus–Organism–Response Theory to examine the gap between positive social media perceptions, trust, and purchase intention. Data were collected from 403 purposively selected respondents through online questionnaires and analyzed using PLS-SEM with SmartPLS. The results show that SMMA has significant positive effects on brand trust, brand image, and purchase intention. Brand image also has a significant positive effect on purchase intention, whereas brand trust does not significantly influence purchase intention. Furthermore, brand image partially mediates the relationship between SMMA and purchase intention, while brand trust does not exhibit a significant mediating effect. Should prioritize visually engaging content, direct call-to-action messages, and social commerce features to strengthen brand image and drive consumer conversion. These findings provide practical guidance for developing more effective social media marketing strategies to enhance consumer purchase intention.